Analysis of Different Rotor and Stator Structures in Order to Optimize Two-Phase Switch Reluctance Motor Torque Characteristics - Allahyari, Arash; Mousavi, Sadra; Nazarpour, Daryoush (IEEE, 2019)
This paper proposes different structures of stator and rotor for 4/2 switch reluctance motor in order to maximize the torque and minimize the dead zone. Different designs for optimization are introduced. Parametric analysis of the variables for the aforementioned purposes conducted utilizing finite element method. Firstly, a conventional 4/2 switch reluctance is simulated utilizing finite element method (FEM). Secondly, different rotor and stator structures such as a four-step axial rotor, radial stepper rotor, stator pole manipulation and mixed structures of the rotor and stator are investigated in order to maximize torque and minimize the dead zone. Finally, a comparison between main design factors for a 4/2 switch reluctance motor is introduced according to the results.